2021
DOI: 10.1007/s12663-021-01560-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Ultrasonography as an Additional Diagnostic Tool for Deciding Management Protocol of Odontogenic Superficial Fascial Space Infections: A Prospective Clinical Study

Abstract: Objective To explore the efficacy of ultrasonography as an additional diagnostic tool in superficial odontogenic fascial space infections of maxillofacial region and modifying the treatment plan when needed. Materials and Methods Forty patients with superficial fascial space infections underwent a detailed clinical, plain radiological and ultrasonographic examination. Based on the ultrasonographic findings, final diagnosis was made and compared with clinical findings. Patients diagnosed with cellulitis were gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Pulp necrosis caused by caries, trauma, periodontal infections, pericoronitis or any of these may lead to most odontogenic infections in healthy patients. [14] In this study, the most frequently involved space was buccal space followed by submandibular space, that is in accordance with some studies [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pulp necrosis caused by caries, trauma, periodontal infections, pericoronitis or any of these may lead to most odontogenic infections in healthy patients. [14] In this study, the most frequently involved space was buccal space followed by submandibular space, that is in accordance with some studies [15].…”
Section: Discussionsupporting
confidence: 91%
“…The most affected tooth was mandibular first molar both in males (10) and in females (15). In a total of 60 cases, clinical diagnosis of cellulitis was made in 18 cases (30 %) and that of abscess in 42 patients (70.0 %).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of studies showed a male prevalence in maxillofacial infections of odontogenic origin [7][8][9] . However, in the present study, a slight prevalence of females was observed in 52% of the sample.…”
Section: Discussionmentioning
confidence: 99%